Tom and Jerry : Shiver me whiskers [videorecording (DVD)] - Jeralds, Scott; Richardson, Kevin Michael; Najimy, Kathy; Reilly, Charles Nelson; Shawn, Wallace; Hamill, Mark; Castellaneta, Dan; Watters, Mark, 1955-; Hanna, William, 1910-2001; Barbera, Joseph (Tom and Jerry, 2006)
It's a swashbuckling pirate adventure when Tom sails with the biggest, baddest pirate on the high seas, the infamous Captain Red. To find buried treasure, Tom and Jerry work together to get past the coconut-throwing monkeys, a giant octopus, and more!